Stable sub‐micrometre high‐flux probe for soft X‐ray ARPES using a monolithic Wolter mirror. (10th July 2020) - Senba, Yasunori; Kishimoto, Hikaru; Takeo, Yoko; Yumoto, Hirokatsu; Koyama, Takahisa; Mimura, Hidekazu; Ohashi, Haruhiko
Abstract : A monolithic Wolter‐type mirror with large acceptance, achromatism and small comatic aberration was designed and evaluated at the soft X‐ray beamline BL25SU of SPring‐8. Abstract : A focusing optics that can provide a sub‐micrometre high‐flux probe for soft X‐ray micrometre‐scale angle‐resolved photoemission spectroscopy (ARPES) is proposed. A monolithic Wolter‐type mirror with a large acceptance, achromatism and small comatic aberration was designed and evaluated. A focused beam size of 0.4 µm (vertical) × 4 µm (horizontal), a high throughput of 59% and a high tolerance of 1.6 mrad to the pitching error were realized at a photon energy of 1000 eV. A Wolter‐type mirror can be practically employed as a stable sub‐micrometre focusing mirror with high throughput in ARPES applications.